SIGNIFICANCE OF INTRACYSTIC PRESSURE IN ABDOMINAL HYDATID-DISEASE - YEGEN, ŞEVKET CUMHUR (BLACKWELL SCIENCE LTD, 1992)
A prospective study was performed in 32 patients (24 female, eight male) with 50 abdominal hydatid cysts, to assess whether intracystic pressure (ICP) could predict viability. The median ICP, measured during operation, was 35 cmH2O for 31 viable cysts and zero for nine non-viable cysts located in the liver (P < 0.05). The median ICP was significantly higher in cysts located in the left lobe of the liver than in those in the right (P < 0.05). The ICP was not significantly different in unilocular or multilocular cysts. ICP increased as the diameter of the cysts increased. The sensitivity of the indirect haemagglutination test was 86 per cent and the specificity 75 per cent. It is concluded that measurement of ICP is a simple and reliable method for assessment of the viability of abdominal hydatid cysts.
Keywords: ECHINOCOCCUS-GRANULOSUS; LIVER